Homa bay earthquakes, 1968 : mud craters and microtumors - Ouma, Joseph Pius Ben Muga.
East African 7th symposium, Kampala, 16th - 20th September, 1969.
AR/MISR/99/8/1
English
Shelf no. 1.
Keywords: Earthquakes